PERSEPSI GURU DALAM IMPLEMENTASI KURIKULUM MERDEKA DI SD NEGERI 01/VII PASAR SAROLANGUN - Hevy Kurnia Dwi Lestari; Juliansyah Putra; Farhan Yadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine teachers' perceptions of the implementation of the Independent Curriculum at SD Negeri 01/VII Pasar Sarolangun. The background of the study arose due to teachers' varying understandings, limited training, and obstacles in preparing teaching materials and implementing differentiated learning. The research method used a qualitative approach through observation and interviews. Using the analysis technique of Miles Hubermen, 2009. The results showed that teachers generally had a positive perception because the Independent Curriculum was considered to provide space for creativity, and more flexible learning in developing learning, and creatively according to needs. although some teachers still experienced technical and adaptation obstacles. Overall, the Independent Curriculum was considered to create more effective and student-centered learning.